Environmental controls on sap flow in black locust forest in Loess Plateau, China. Issue 1 (December 2017) - Ma, Changkun; Luo, Yi; Shao, Mingan; Li, Xiangdong; Sun, Lin; Jia, Xiaoxu
Abstract Black locust accounts for over 90% of artificial forests in China's Loess Plateau region. However, water use of black locust is an uphill challenge for this semi-arid region. To accurately quantify tree water use and to explain the related hydrological processes, it is important to collect reliable data for application in the estimation of sap flow and its response to environmental factors. This study measured sap flow in black locust in the 2015 and 2016 growth seasons using the thermal dissipation probes technique and laboratory-calibrated Granier's equation. The study showed that the laboratory calibrated coefficient α was much larger than the original value presented by Granier, while the coefficient β was similar to the original one. The average daily transpiration was 2.1 mm day−1 for 2015 and 1.6 mm day−1 for 2016. Net solar radiation (Rn ) was the key meteorological factor controlling sap flow, followed by vapor pressure deficit (VPD ) and then temperature (T ).VPD had a threshold control on sap flow at threshold values of 1.9 kPa for 2015 and 1.6 kPa for 2016. The effects of diurnal hysteresis ofRn, VPD andT on sap flow were evident, indicating that black locust water use was conservative.